2012
DOI: 10.1073/pnas.1202492109
|View full text |Cite
|
Sign up to set email alerts
|

Dual blockade of lipid and cyclin-dependent kinases induces synthetic lethality in malignant glioma

Abstract: Malignant glioma, the most common primary brain tumor, is generally incurable. Although phosphatidylinositol-3-kinase (PI3K) signaling features prominently in glioma, inhibitors generally block proliferation rather than induce apoptosis. Starting with an inhibitor of both lipid and protein kinases that induced prominent apoptosis and that failed early clinical development because of its broad target profile and overall toxicity, we identified protein kinase targets, the blockade of which showed selective synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 25 publications
1
37
0
1
Order By: Relevance
“…Cheng et al reported that PIK-75 could block Cdk1 and Cdk2 and induce cell cycle arrest and apoptosis in glioblastoma cell lines. 29 However, we and others have shown that the affinity of PIK-75 for Cdk2 is .100-fold lower (Kd 5 540 nM) than Cdk9 (Kd 5 4.1 nM; Figure 3B). 30 In addition, our results indicate that PIK-75 is able to induce apoptosis in the CD341CD38-CD1231 population enriched for quiescent leukemic stem/progenitor cells (Figure 1), suggesting that a cell cycle block is not a prerequisite for the induction of cell death.…”
Section: Pik-75 Inhibits Cdk7 and Cdk9 Resulting In A Block Of Mcl-1mentioning
confidence: 99%
“…Cheng et al reported that PIK-75 could block Cdk1 and Cdk2 and induce cell cycle arrest and apoptosis in glioblastoma cell lines. 29 However, we and others have shown that the affinity of PIK-75 for Cdk2 is .100-fold lower (Kd 5 540 nM) than Cdk9 (Kd 5 4.1 nM; Figure 3B). 30 In addition, our results indicate that PIK-75 is able to induce apoptosis in the CD341CD38-CD1231 population enriched for quiescent leukemic stem/progenitor cells (Figure 1), suggesting that a cell cycle block is not a prerequisite for the induction of cell death.…”
Section: Pik-75 Inhibits Cdk7 and Cdk9 Resulting In A Block Of Mcl-1mentioning
confidence: 99%
“…Treatment of a wild‐type PTEN cell line with the PTEN inhibitor bisperoxovanadium in combination with PI‐75 caused increased phosphorylation of Akt and attenuated cell death without affecting G2/M arrest. Surprisingly, computational studies indicated that PI‐75 is also a strong inhibitor of CDK1 and 2 . While the inhibition of single CDKs (CDK1 or CDK2) or CDK1 and PI3Kα had no impact on apoptosis in glioma cells expressing wild‐type PTEN, combined CDK2 and PI3Kα inhibition increased cell death, albeit to a lesser extent than was observed following PI‐75 treatment.…”
Section: Synthetic Lethality Of Cdk Inhibitors In the Treatment Of Spmentioning
confidence: 97%
“…Further, chemical/genetic screens suggest that the concept of synthetic lethality can be applied to the use of CDK inhibitors against cancer. Specifically, inhibiting CDK2 in tumors that overexpress N-myc or c-Myc may induce synthetic lethality, and coinhibition of CDK2 and phosphatidylinositol 39-kinase is also synthetically lethal (Molenaar et al, 2009;Cheng et al, 2012;Etemadmoghadam et al, 2013;Li et al, 2015).…”
Section: Future Opportunitiesmentioning
confidence: 99%